Pemanfaatan Bonggol Pisang untuk Dijadikan Nugget yang Bernilai Gizi Tinggi Serta Ekonomis di Desa Ilih Kecamatan Damer Kabupaten Maluku Barat Daya - Inggrid Welerubun (Jurnal Pengabdian Masyarakat Nusantara, 2026)
This community service initiative aims to enhance the knowledge and skills of the residents of Ilih Village, Damer District, Southwest Maluku Regency, regarding the use of banana corms as a nutritious and cost-effective alternative food source. Banana corms have historically been underutilized and generally treated merely as agricultural waste. Through training and mentoring sessions, the community was educated on the nutritional content of banana corms, processing techniques, and business opportunities for home-based banana corm nugget production. The methods employed included outreach, demonstrations, hands-on nugget-making training, and an evaluation of the activity's outcomes. The results indicate a high level of community enthusiasm for the innovation of processing banana corms into nuggets. Following the activity, participants demonstrated increased knowledge regarding the utilization of local food ingredients, hygienic processing techniques, and the economic potential of the processed product. The banana corm nuggets offered a pleasant taste and appealing texture, and were well-received by the community. Furthermore, the product's low production cost suggests it could serve as a source of additional income for villagers. This initiative is expected to support local food security and improve community welfare through the development of food businesses based on local resources.